Financial Dollarization Equilibria : A Framework for Policy Analysis - Ize, Alain (Washington, D.C. : International Monetary Fund, 2005)
Rapidly rising dollarization and numerous related financial crises in recent years have heightened the need for policy action. This paper contributes to the policy debate by presenting a common analytic framework that examines the roots of de facto financial dollarization under different economic environments and analyzes its interplay with monetary and prudential policies. In addition to providing a systematic analysis of the existence, stability, and multiplicity of dollarization equilibria, the paper makes a few novel contributions. In particular, it stresses the key role played by monetary policy endogeneity and identifies the underlying determinants of the peso premium that are responsible for inducing a preference for the dollar in financial transactions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet